Tumour-free distance: a novel prognostic marker in patients with early-stage cervical cancer treated by primary surgery - Cibula, David; Slama, Jiri; Dostálek, Lukáš; Fischerová, Daniela; Germanova, Anna; Frühauf, Filip; Dundr, Pavel; Nemejcova, Kristyna; Jarkovsky, Jiri; Sebestova, Silvie; Burgetová, Andrea; Borčinová, Martina; et al. (British journal of cancer, 2021)
BACKGROUND: Models predicting recurrence risk (RR) of cervical cancer are used to tailor adjuvant treatment after radical surgery. The goal of our study was to compare available prognostic factors and to develop a prognostic model that would be easy to standardise and use in routine clinical practice. METHODS: All consecutive patients with early-stage cervical cancer treated by primary surgery in a single referral centre (01/2007-12/2016) were eligible if assessed by standardised protocols for pre-operative imaging and pathology. Fifteen prognostic markers were evaluated in 379 patients, out of which 320 lymph node (LN)-negative. RESULTS: The best predictive model for the whole cohort entailed a combination of tumour-free distance (TFD) ≤ 3.5 mm and LN positivity, which separated two subgroups with a substantially distinct RR 36% and 6.5%, respectively. In LN-negative patients, a combination of TFD ≤ 3.5 mm and adenosquamous tumour type separated a group of nine patients with RR 33% from the rest of the group with 6% RR. CONCLUSIONS: A newly identified prognostic marker, TFD, surpassed all traditional tumour-related markers in the RR assessment. Predictive models combining TFD, which can be easily accessed on pre-operative imaging, with LN status or tumour type can be used in daily practice and can help to identify patients with the highest RR.
Keywords: hysterektomie; lymfatické uzliny; retrospektivní studie; Survival Rate; lokální recidiva nádoru; Lymph Nodes; následné studie; Uterine Cervical Neoplasms; prognóza; nádory děložního čípku; Adult; Aged; dospělí; senioři; Follow-Up Studies; Neoplasm Recurrence, Local; Hysterectomy; lidé; ženské pohlaví; adenokarcinom; Humans; Prognosis; Retrospective Studies; Adenocarcinoma; spinocelulární karcinom; Female; lidé středního věku; míra přežití; Carcinoma, Squamous Cell; Middle Aged